Potensi Biji Durian(Durio zibethinus) di Kota Padang Sebagai Sumber Karbon untuk Material Maju - Oktavia Wulandari; Umar Kalmar Nizar (Departemen Kimia FMIPA UNP, 2023)
Indonesia is a maritime country that has a lot of natural resources, but the processing of these resources is still lacking. One of the efforts to develop these natural resources is in the form of advanced materials. The purpose of this research is to analyze and determine the optimal temperature of durian seed carbon. Carbon is synthesized through a calcination process with a temperature variation of 250oC-400oC for 1 hour. The carbon obtained was tested for ash content, vapor content and analysis of bound carbon content. Based on the results of the study which showed that the higher the temperature, the higher the ash content, while the vapor and bound carbon content decreased. The optimal result in this study which is in accordance with SNI-06-3730-1995 is durian seed carbon with a calcination temperature of 250oC.